Financial knowledge and investment choices: Evidence from individual investors in the Nepal stock exchange - Binay Shrestha; Neha Agrawal; Sneha Chaurasiya; Nirdosh Agarwal; B.M. Sajedul Karim; Asma Khan (Journal of Commerce, Management, and Tourism Studies, 2026)
Financial knowledge has become an essential determinant of investment behaviour, particularly in emerging capital markets where individual investors often encounter information asymmetry and market volatility. This study aims to examine the influence of financial knowledge on the investment choices of individual investors participating in the Nepal Stock Exchange (NEPSE). Specifically, it investigates how investors' understanding of financial concepts, risk diversification, portfolio management, and market information contributes to rational investment decision-making. This study employed a quantitative research design using a cross-sectional survey. Primary data were collected through structured questionnaires distributed to individual investors actively trading on the Nepal Stock Exchange. A purposive sampling technique was adopted to select respondents with investment experience in the stock market. The collected data were analysed using descriptive statistics, reliability and validity tests, Pearson correlation analysis, and multiple regression analysis to examine the relationship between financial knowledge and investment choices. The findings indicate that financial knowledge has a positive and statistically significant influence on investment choices. Investors with higher levels of financial knowledge demonstrate greater confidence in evaluating investment opportunities, diversifying portfolios, managing financial risks, and making informed investment decisions. Furthermore, financial knowledge reduces reliance on speculative behaviour and emotional decision-making while encouraging systematic investment strategies based on market information and financial analysis. The study concludes that enhancing financial knowledge among individual investors can improve the quality of investment decisions and promote more efficient participation in Nepal's capital market. These findings provide valuable implications for policymakers, financial institutions, regulatory authorities, and investor education programs seeking to strengthen financial capability and foster sustainable growth in the Nepal Stock Exchange.